Targeting lean process improvement projects for maximum financial impact. Issue 2 (25th January 2016) - Darlington, John; Francis, Mark; Found, Pauline; Thomas, Andrew
Abstract : This empirical paper details a 12-month applied research project at a UK low-volume manufacturer of large vehicles. The industry problem from which this study originates was a concern over the subjective nature with which the firm's existing lean intervention projects were being targeted (prioritised and selected). A structured literature review on this topic was unable to identify any objective decision support mechanism for doing so; one that encompassed financial as well as operational criteria. The resultant study was organised around an established seven-step action research framework. The main body of evidence was derived from extensive analysis of financial and operational data extracted from the firm's enterprise resource planning system, along with two structured workshops that each involved multiple informants drawn from the firm's production centres and its accountancy department. Supplementary primary research was provided in the guise of numerous unstructured interviews to validate data and from observation of shop floor practices. The main contribution of this article is identifying and addressing the gap highlighted above, by developing and testing a financially driven method for objectively targeting process improvement interventions within this large and geographically dispersed operation. This innovative method includes five new constituent techniques.